Performance analysis of a new OCFHC/QCC vis‐a‐vis synchronous PC/OOC code using photon count approach. Issue 2 (1st April 2019) - Yadav, Ajay; Kar, Subrat; Jain, Virander Kumar
Abstract : In this study, the performance of one‐coincidence frequency hopping code/quadratic congruence code (OCFHC/QCC) has been analysed and compared with an existing code. The error probabilities of an eight‐user optical code division multiple access (OCDMA) system are 4.7934 × 10 − 9 and 5.9497 × 10 − 10 for the synchronous prime code/optical orthogonal code (PC/OOC) and OCFHC/QCC, respectively, at the received power level −15 dBm and data rate 1 Gbps. The improvement in the performance is of the order of 10 − 1 which becomes better if the received power level increases beyond −15 dBm. In addition, the effect of variation in code weight, code length and number of wavelengths of the OCFHC/QCC code on the performance of the OCDMA system is also studied. OCFHC/QCC has a simple design methodology, flexibility in choosing the number of wavelengths, large cardinality and superior performance than the synchronous PC/OOC. Furthermore, the performance of the OCFHC/QCC is also analysed in the atmospheric channel. Based on the analysis, it is concluded that this code should be preferred for local area network, multicode keying, and wireless optical communication.